Effects of rice husk fibers on the properties of mixed-particle-size fiber-reinforced polyvinyl chloride composites under soil accelerated aging conditions. (September 2019) - Wang, Lei; He, Chunxia
In this article, rice husk fiber/polyvinyl chloride composites were prepared and analyzed. The optimal composition of mixed-particle-size fiber-reinforced composites was determined through orthogonal experimentation. The physical, mechanical, and thermal properties of the mixed-particle-size fiber-reinforced composites were compared to unprocessed (100 mesh) rice husk fiber/polyvinyl chloride composites. The surface microscopic appearances of the unprocessed and final composites were observed via laser microscope. Long-term accelerated soil aging caused micro-cracks to appear on the surfaces of the composites. Interfacial adhesion was observed via scanning electron microscopy. The results indicated that mixed-particle-size fibers can better fill interfacial gaps, leading to strong interfacial adhesion. Furthermore, the addition of mixed-particle-size fibers improves the soil aging resistance of composites. The hardness, flexural strength, impact strength, and first onset pyrolysis temperature (after 0 days) increase from 50 HRR, 35.2 MPa, 3.19 KJ/m 2, and 258.5°C to 55 HRR, 39.4 MPa, 3.86 KJ/m 2, and 261.2°C, respectively. However, the mass loss rate and thickness expansion rate (after 21 days) decrease from 2.9% and 0.79% to 2.21% and 0.74%, respectively. In general, the addition of mixed-particle-size fibers improves the ultimate properties of composites under soil aging conditions.